2006
DOI: 10.1111/j.1742-4658.2006.05464.x
|View full text |Cite
|
Sign up to set email alerts
|

The Emery–Dreifuss muscular dystrophy associated‐protein emerin is phosphorylated on serine 49 by protein kinase A

Abstract: Emerin is a ubiquitously expressed inner nuclear membrane protein of unknown function. Mutations in its gene give rise to X-linked Emery-Dreifuss muscular dystrophy (X-EDMD), a neuromuscular condition with an associated life-threatening cardiomyopathy. We have previously reported that emerin is phosphorylated in a cell cycle-dependent manner in human lymphoblastoid cell lines [Ellis et al. (1998) Aberrant intracellular targeting and cell cycle-dependent phosphorylation of emerin contribute to the EDMD phenotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 44 publications
1
29
0
Order By: Relevance
“…Consequently, the opsin tag with its N-glycosylation site must have reached the microsomal lumen, confirming membrane insertion of the tail-anchored protein. Addition of lambda-phosphatase largely abolished the smear of higher molecular mass forms, in agreement with earlier observations that emerin can be phosphorylated (Ellis et al, 1998;Leach et al, 2007;Roberts et al, 2006). TRC40-dependent membrane integration of tail-anchored proteins is an active, ATP-dependent process (Favaloro et al, 2008(Favaloro et al, , 2010Stefanovic and Hegde, 2007).…”
Section: Post-translational Membrane Integration Of Emerin By the Trcsupporting
confidence: 75%
“…Consequently, the opsin tag with its N-glycosylation site must have reached the microsomal lumen, confirming membrane insertion of the tail-anchored protein. Addition of lambda-phosphatase largely abolished the smear of higher molecular mass forms, in agreement with earlier observations that emerin can be phosphorylated (Ellis et al, 1998;Leach et al, 2007;Roberts et al, 2006). TRC40-dependent membrane integration of tail-anchored proteins is an active, ATP-dependent process (Favaloro et al, 2008(Favaloro et al, , 2010Stefanovic and Hegde, 2007).…”
Section: Post-translational Membrane Integration Of Emerin By the Trcsupporting
confidence: 75%
“…We predict that post-translational modification of Lmo7 or emerin, or both, increases their affinity for one another. Emerin contains four serine, one threonine and 13 tyrosine residues that are phosphorylated in vitro and in vivo (Amanchy et al, 2005;Brill et al, 2004;Hirano et al, 2005;Roberts et al, 2006;Schlosser et al, 2006), many of which regulate binding to its partners (Hirano et al, 2005;Roberts et al, 2006;Tifft et al, 2009). However, it is not well documented how emerin phosphorylation changes during myogenic differentiation.…”
Section: Emerin Regulates Lmo7 Binding To and Activation Of Myogenic mentioning
confidence: 99%
“…It has been previously demonstrated that emerin is phosphorylated; hence, the higher molecular weight isoform we detected in fibroblasts Y259X/Y259X may be phosphorylated [20][21][22][23][24]. To assess whether the protein with an apparent molecular mass of 36 kDa recognized by antiemerin antibodies was a phosphorylated form of emerin, we treated fibroblasts Y259X/Y259X with the phosphatase inhibitor okadaic acid (OA).…”
Section: Effect Of Lack Of A-type Lamins In Cells Homozygous For the mentioning
confidence: 99%